MODEL ALTMAN Z-SCORE TERHADAP KINERJA KEUANGAN DI BURSA EFEK INDONESIA MELALUI PENDEKATAN REGRESI LOGISTIK - Nurul Fitri; Rachma Zannati (AKURASI: Jurnal Riset Akuntansi dan Keuangan, 2019)
The purpose of this study is to confirm the determinants of financial performance on the condition of financial distress companies through the Altman Model (Z-score) approach. The sample in this study is a manufacturing industry sub-sector company which is listed on the Indonesia Stock Exchange for the period 2013 to 2017. The analysis technique of this study uses logistic regression analysis, and the findings prove that the Current Ratio and Debt to Equity Ratio cannot predict the condition of Financial Distress. Whereas Return On Assets can predict Financial Distress in manufacturing companies. The implications of this finding can contribute to companies in maintaining financialperformance stability so as to avoid financial distress.